To be or not to be oxidized: A case study of olivine behavior in the fusion crust of ureilite A 09368 and H chondrites A 09004 and A 09502 - Pittarello, Lidia; Yamaguchi, Akira; Roszjar, Julia; Debaille, Vinciane; Koeberl, Christian; Claeys, Philippe (2019)
Meteorite fusion crusts are quenched melt layers formed during meteoroid atmospheric entry, mostly preserved as coating on the meteorite surface. Antarctic ureilite Asuka (A) 09368 and H chondrites A 09004 and A 09502 exhibit well preserved thick fusion crusts, characterized by extensive olivine crystallization. As olivine is one of the major components of most meteorites and its petrologic behavior is well constrained, it can be roughly considered as representative for the bulk meteorite. Thus, in this work, the evolution of olivine in fusion crusts of the above-listed selected samples is investigated. The different shape and chemistry of olivine crystallized in the fusion crust, both as overgrown rim on relic olivine clasts and as new crystals, suggest a general temperature and cooling rate gradient. The occurrence of reverse and oscillatory zoning in individual olivine grains within the fusion crust suggests complex redox reactions. Overall, the investigated fusion crusts exhibit a general oxidation of the relatively reduced initial material. However, evidence of local reduction is preserved. Reduction is likely triggered by the presence of carbon in the ureilite or by overheating during the atmospheric entry. Constraining these processes provides a potential analog for interpreting features observed in cosmic spherules and micrometeorites and for calibrating experiments and numerical models on the formation of fusion crusts. ©2019 The Authors. Meteoritics & Planetary Science published by Wiley Periodicals, Inc. on behalf of The Meteoritical Society (MET). SCOPUS: ar.j info:eu-repo/semantics/published